Modulation of hydrogen peroxide-induced oxidative stress in human neuronal cells by Thymoquinone-rich fraction and Thymoquinone via transcriptomic regulation of antioxidant and apoptotic signaling genes - Ismail, Norsharina; Ismail, Maznah; Azmi, Nur Hanisah; Abu Bakar, Muhammad Firdaus; Basri, Hamidon; Abdullah, Maizaton Atmadini (Hindawi Publishing Corporation, 2016)
Nigella sativa Linn. (N. sativa) and its bioactive constituent Thymoquinone (TQ) have demonstrated numerous pharmacological attributes. In the present study, the neuroprotective properties of Thymoquinone-rich fraction (TQRF) and TQ against hydrogen peroxide- (H2O2-) induced neurotoxicity in differentiated human SH-SY5Y cells were investigated. TQRF was extracted using supercritical fluid extraction while TQ was acquired commercially, and their effects on H2O2 were evaluated using cell viability assay, reactive oxygen species (ROS) assay, morphological observation, and multiplex gene expression. Both TQRF and TQ protected the cells against H2O2 by preserving the mitochondrial metabolic enzymes, reducing intracellular ROS levels, preserving morphological architecture, and modulating the expression of genes related to antioxidants (SOD1, SOD2, and catalase) and signaling genes (p53, AKT1, ERK1/2, p38 MAPK, JNK, and NF-κβ). In conclusion, the enhanced efficacy of TQRF over TQ was likely due to the synergism of multiple constituents in TQRF. The efficacy of TQRF was better than that of TQ alone when equal concentrations of TQ in TQRF were compared. In addition, TQRF also showed comparable effects to TQ when the same concentrations were tested. These findings provide further support for the use of TQRF as an alternative to combat oxidative stress insults in neurodegenerative diseases.